ESG-Washing in the mutual funds industry? From information asymmetry to regulation - Bertrand Candelon; Jean-Baptiste Hasse; Quentin Lajaunie (Risks, 2021)
In this paper, we study the asymmetric information between asset managers and investors in the socially responsible investment (SRI) market. Specifically, we investigate the lack of transparency of the extra-financial information communicated by asset managers. Using a unique international panel dataset of approximately 1500 equity mutual funds, we provide empirical evidence that some asset managers portray themselves as socially responsible yet do not make tangible investment decisions. Furthermore, our results indicate that the financial performance of mutual funds is not related to asset managers' signals but should be evaluated relatively using extra-financial ratings. In summary, our findings advocate for a unified regulation framework that constrains asset managers' communication.
Keywords: 330; socially responsible investing (SRI); environmental; social and governance (ESG); asymmetric information; regulation